تأثیر شکل المقطع الطولی للسد الغاطس العریض على انسیابیة الجریان - nan, nan (Iraqi Journal of Civil Engineering, 2008)
One of the most important hydraulic structures which are used in irrigation systems are the broad crested weirs, which can be defined as a vertical barrier in a canal or tank side in which the water may flow freely. This weir can be used to measure the discharge and to raise the water level in the upstream. In this study the effect of longitudinal section on streamlined flow over broad crested weir has been investigated. Loss in energy, working efficiency and the coefficient of discharge have been considered. Experimental study carried out using (25) samples with six different hydraulic heads. The analysis of results indicate that the coefficient of discharge (Cd) increases with increasing Froud Number (Fr) and the most effective slope of upstream and downstream faces of the weir wear (45°) and (60°) respectively, at which the coefficient of discharge demonstrated was (0.644